Stakeholders Synergy for Ciliwung River Management from a Whole of Government Perspective - Hidayaturahmi; Izzul Fatchu Reza; Ridwan Rajab (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2025)
This study aims to analyze inter-actor relations in the management of the Ciliwung River and to identify the strengths, weaknesses, opportunities, and threats in building sustainable collaborative governance. The research employed a qualitative approach with descriptive and evaluative analysis, synthesizing data from various documents and previous studies. The findings indicate that the government remains the most dominant actor due to its regulatory authority and resource capacity, yet it is vulnerable to institutional fragmentation and public pressure. The private sector possesses significant financial and technological potential, but its involvement remains largely philanthropic. Non-governmental organizations (NGOs) emerge as the most effective actors in bridging collaboration among stakeholders through participatory and developmental communication approaches. Academia serves as a source of scientific legitimacy but shows limited capacity in policy translation, while the media strengthens public awareness and social accountability. The IFAS–EFAS analysis positions Ciliwung’s governance within the growth–stability quadrant, reflecting a balance between internal strengths and external opportunities. The study highlights the importance of adopting a Whole of Government and Whole of Society approach to enhance inter-agency coordination, collaborative incentives, and public engagement for sustainable river governance.